Professionalizing Leadership - Kellerman, Barbara (Tantor Media, Inc., 2018)
Over the last forty years, the leadership industry has grown exponentially. Yet leadership education, training, and development still fall far short. Moreover, leaders are demeaned, degraded, and derided as they never were before. Why? The problem is that leadership has stayed stuck. It has remained an occupation instead of becoming a profession. Unlike medicine and law, leadership has no core curriculum that is considered essential. It has no widely agreed on metric, or criteria for qualification. And it has no professional association to oversee the conduct of its members or assure minimum standards. Professionalizing Leadership looks to a past in which learning to lead was the most important of eruditions. It looks to a present in which learning to lead is as effortless as ubiquitous. And it looks to a future in which learning to be a leader might look different altogether-it might resemble the far more rigorous process of learning to be a doctor or a lawyer. As it stands now, the military is the only major American institution that gets it right. It assumes leadership is a profession that requires those who practice it to be taught in accordance with high professional standards. Barbara Kellerman draws on the military experience specifically to develop a template for learning how to lead generally.